Specific features of the synthesis of ceramic-metal materials in an unsteady combustion regime - Lapshin, Oleg V. (Journal of engineering physics and thermophysics)
A mathematical model has been constructed and investigated by numerical methods for unsteady gasless combustion of a binary mixture under the conditions of thermocapillary flow of the melt of one of the components. Various unsteady regimes have been identified for the propagation of a synthesis wave depending on mass concentrations of components and the initial porosity of the mixture. An investigation has been made into the process of forming the macrostructure of synthesis products in a self-sustained oscillating regime of combustion. A possibility in principle has been shown for combustion of mixtures with excess of a low-melting component at a higher rate than in combustion of a mixture of a stoichiometric composition.